Illness understanding in children and adolescents with heart disease. Issue 4 (1st October 2000) - Veldtman, G R; Matley, S L; Kendall, L; Quirk, J; Gibbs, J L; Parsons, J M; Hewison, J
Abstract : AIMS: To evaluate illness knowledge and understanding in children and adolescents with congenital and acquired heart disease, and whether the degree of understanding is related to age, sex, or complexity of the heart disease. DESIGN: Prospective cohort study. SETTING: Tertiary paediatric cardiac centre. METHODS: Patients' understanding of their congenital heart disease was assessed in a representative sample of volunteers aged between 7–18 years using semistructured interviews based upon Leventhal's illness representation model. RESULTS: 63 of 69 interviews were suitable for analysis. There were similar numbers of boys and girls and a wide distribution of heart defects. Only 30% of patients had a good understanding of their illness; 77% did not know the medical name of their condition, and 33% had a wrong or poor understanding of their illness. Understanding was unrelated to age, sex, or the nature of the heart disease. Understanding of illness duration was significantly related to age, but not to sex or to the nature of the disease. CONCLUSIONS: Illness understanding is poor in children and adolescents with heart disease, and many have an entirely wrong concept of their disease. Intensified efforts to ensure better patient and parental understanding are needed.